Ultrasound Provides a Reliable Test of Local Anesthetic Spread. Issue 4 (1st June 2010) - McCartney, Colin J. L.; Dickinson, Victoria; Dubrowski, Adam; Riazi, Sheila; McHardy, Paul; Awad, Imad T.
Abstract : Background and Objectives: We predicted that practitioners could identify injectate spread in a model of ultrasound-guided peripheral nerve block. Methods: Both novices and experts in ultrasound-guided peripheral nerve block were asked to recognize the spread of local anesthetic in a gelatin ultrasound phantom. In a blinded and randomized fashion, these participants were observed to either successfully or unsuccessfully state whether an injection had been made. Results: Twelve novices and 8 experts each completed the trials. Accuracy, Sensitivity and specificity were calculated for all trials. Users attained a very high accuracy and sensitivity (>85%) as well as specificity (>90%) with ultrasound in this model. Conclusions: This study shows that ultrasound is a reliable method of detecting injectate spread in a gelatin phantom model.